Liberation Conscience in Prakash Jha’s Lipstick Under My Burka - Gurung, Gol Man (Interdisciplinary Journal of Management and Social Sciences, 2023)
Prakash Jha's movie Lipstick Under My Burka deals with the story of four Indian Women's search for strength and liberation in their lives. The research particularly veers around the double marginalized women in Indian society. Characters presented in the movie are exploited economically and politically on the one hand and sexually on the other. Alankrita Shrivastava-the director of the movie uses cinematography to depict the gruesome situation of the domination with the help of four female characters where some are forced to have sex whereas some are deprived of it. Rahim Aslam, husband of Shereen uses his wife as sex dolly. Barren land among husband and wife is flourishes vigorously, whenever Rahim feels sexual desire he straightforwardly moves towards Shereen in order to fulfill his libido.